Crassocephalum crepidioides (Ebolo) Protect against Paracetamol- Induced Hepatotoxicity in Wistar Rats - Mudathir, Fausat K. Ola; Onoharigho, Ogheneoruese F.; Jeje, Sikirullai O.; Ajekevwoda, Ighorhiowhoaro M. (International Journal of Scientific Research in Biological Sciences, 2022)
Paracetamol causes hepatocellular damage due to increase oxidative stress, whereas Crassocephalum crepidioides enhances antioxidant status. The preventive function of Crassocephalum crepidioides against paracetamol (PCM)-induced hepatocellular oxidative damage was studied. The experiment was made up of four groups (1, 2, 3, and 4) of Wistar rats (n=6). The control (Group 1) were given distilled water while groups 2 and 3 animals were given 300mg/kg bwt/day methanol extract of C. crepidioides leaves (MECL) and 250 mg/kg bwt/day PCM respectively for two weeks. Group 4 was given (MECL) for one week and thereafter a concurrent dose of 300 mg per kg bwt each day (MECL) and 250 per kg bwt each day PCM for two weeks. All administration was done orally. The evaluation of serum aspartate amino transferase (AST) and Alanine amino transferase (ALT) activities were carried out to detect liver injury. Glutataione-s-transferase (GST), superoxide dismutase (SOD), catalase activities and reduced glutathione (GSH) level were utilized to measure antioxidant status. Malondialdehyde (MDA) level was employed as an indication of lipid peroxidation. The results indicated an increase (p< 0.05) in the activities of serum AST, ALT and MDA level in the PCM group. The activities of GST, SOD, catalase and level of GSH were significantly lowered (p< 0.05) relative to control. Concurrent treatment with PCM and C. crepidioides considerably decreased (p< 0.05) MDA level, AST and ALT activities but significantly increased (p< 0.05) the antioxidant enzymes compared to PCM group. Finally, Crassocephalum crepidioides may protect Wistar rat’s liver against paracetamol-induced oxidative damage.